A CFD–FEA two-way coupling method for predicting ship wave loads and hydroelastic responses. (December 2021) - Jiao, Jialong; Huang, Songxing; Wang, Shan; Guedes Soares, C.
Abstract: This paper presents a co-simulation method for numerical prediction of nonlinear hydroelastic response of ship advancing in severe wave conditions. Two-way coupling of CFD and FEA solvers is applied where the external fluid pressure exported from the CFD simulation is used to derive the structural responses in the FEA solver and the structural deformations are fed back into the CFD solver to deform the mesh. Violent free surface flow such as slamming and green water on deck is well captured by the RANS and VOF techniques in the CFD solver. The nonlinear whipping and springing responses can be accurately simulated by the structural solver through the dynamic 3D FEA of the hull. By conducting co-simulations with a standard S175 containership, the developed fully coupled method was proved to be capable and reliable in accurate simulating almost all the physical characteristics of interests within the scope of ship seakeeping and hydroelasticity, which include large-amplitude motions, accelerations, wave loads, slamming loads, green water loads and whipping and springing responses of the hull in waves.